Synthesis of 2-Phenoxyacetic Acid Analogs for Evaluation of the Anti-inflammatory Potential and Subsequent In Silico Analysis - Hossain, Md. Mofazzal; Biswas, Bishyajit Kumar; Bepary, Sukumar (Universitas Gadjah Mada, 2024)
Several 2-phenoxyacetic acid derivatives and their isosteres were synthesized in moderate to high yield (57–96%) for searching newer and safer alternatives to these existing anti-inflammatory agents. The compounds were characterized by 1H-NMR, 13C-NMR and HRMS. The synthesized compounds have been subjected to in vitro anti-inflammatory activity using egg albumin denaturation and human red blood cell membrane stabilization methods. The compounds were also evaluated for their anti-inflammatory activity in the mice model. The synthesized compounds were subsequently subjected to docking analysis. The in vitro pharmacokinetic properties were analyzed by applying the pkCSM software and drug-likeness was checked by using Lipinski’s rule. Some synthesized esters and amides, like SM61, SM81, SM82, SM83, SM91 and SM101, were significantly more powerful as anti-inflammatory agents. The efficacies were correlated with their orientations in the binding pocket of the cyclooxygenase enzyme. The encouraging in vitro and in vivo activities, the optimum pharmacokinetic profile, and good drug-likeness indicated that these scaffolds could be considered for future discovery of newer nonsteroidal anti-inflammatory drugs (NSAIDs).